Design Of A Multi-Band RF Energy Harvesting Rectenna With Harmonics Suppression Capability - Mohd Noor, Faza Syahirah (2020)
In recent years, rectenna with the ability of energy harvesting has been gaining tremendous interests by researchers. Constant availability of radio frequency (RF) signals at which it is being deployed both at indoor and outdoor environment favors these types of signals as the optimum choice of energy to be harvested considering its continuous operation. The design and development of RF energy harvesting is fit to describe the transmission of power wirelessly. RF signals which is in form of alternating current (AC) is being radiated through electromagnetic (EM) waves into the environment and rectenna structure will capture the RF signals and therefore converts it into direct current (DC) signals. Rectenna which constructed upon the integration of antenna and rectifier structure within the same physical structure explains the ability of rectenna in harvesting and rectifying AC signals into DC signals. The antenna is to receive or capture the RF signals at which it is then being rectified into DC signals by the rectifier. The integration of both antenna and rectifier structures contribute to the creation of harmonics due to the non-linear behavior of active elements such as Schottky diode and capacitor at the rectifier circuit. Hence, harmonics suppression filter design is proposed to suppress the harmonics generated. This thesis presents a design of rectenna structure with multi-band characteristics and harmonics suppression capability. Multi-band characteristics of operating frequency at 2.45GHz and 5.80GHz are achieved using inverted π-shaped coupling slot while the ability of harmonics suppression is achieved through the introduction of embedded U-slot and asymmetrical right-and-left-handed stubs at the antenna transmission feedline. The addition of slot and stubs at the transmission feedline has replaced the conventional filter structure which is larger in size. In order to enhance the gain of antenna, aperture-coupled antenna is constructed with air gap through the simulation using Computer Simulation Technology (CST) software. Meanwhile, the rectifier of double-diode configuration circuit of the rectenna is designed and simulated using Advanced Design System (ADS) with rectifying element HSMS286B Schottky diodes and interdigital capacitor. The structure interdigital capacitor in the form of transmission line is applied to replicate the series-configuration active capacitor component. The development of the rectenna prototype is executed using FR-4 substrate material with dielectric constant of 4.3 and thickness of 1.6mm. The antenna is able to suppress third and higher-order harmonics ranging from 6.12GHz up to 10.00GHz and achieve the gain of 7.05dBi and 0.94dBi at the operating frequency 2.45GHz and 5.80GHz, respectively. The double-diode rectifier prototype can be operated at both 2.45GHz and 5.80GHz hence, maximum RF-to-DC conversion efficiency of 92.26% for frequency 2.45GHz and 30.14% for frequency 5.80GHz is achieved, each with the RF input power of 20dBm and 25dBm respectively. The rectenna design proposed does not only possessed the characteristic of a multi-band, but also the has the harmonics suppression ability for the purpose of improving the RF-to-DC conversion efficiency thus makes it appropriate for the application of wireless power transmission.